Predictors of fear of diabetes progression: A multi-center cross-sectional study for patients self-management and healthcare professions education - Wang, Yanhao; Yu, Qiuhua; Zeng, Zihuan; Yuan, Ruizhu; Wang, Ruiding; Chen, Jianli; Zhou, Hengyu; Tang, Jiao (Frontiers in Public Health, 2022)
Objective Excessive fear of progression can affect the mental health, social function, and wellbeing of patients with chronic diseases. This study investigated the fear of progression (FoP) and the socio-demographic and clinical predictors among patients with type 2 diabetes mellitus (T2DM). Method The present study is a multi-center cross-sectional study. Inpatients with T2DM were recruited by a multi-stage convenience sampling method from the department of endocrinology in 5 tertiary hospitals in Southwest China. 459 T2DM patients were consecutively enrolled. Socio-demographic, clinical data, and answers to the fear of progression questionnaire (FoP-Q) were collected. Results 385 patients with complete data were eligible. The average score of FoP-Q-SF was 26.84 and 23.1% of patients reached the dysfunctional fear of progression criterion. The greatest fears were worrying about “disease progression,” “the adverse reactions of medication,” and “relying on strangers for activities of daily living.” Health education (P < 0.001), age (P = 0.002), hypoglycemia history (P = 0.006), employment status (P = 0.025) and duration since being diagnosed with type 2 diabetes mellitus (P = 0.032) were the related factors of fear of progression. Conclusion Early assessment of the fear of progression was imperative to identify dysfunctional fear of progression in patients with type 2 diabetes mellitus. Meanwhile, the meaning of these predictors for strengthening healthcare professions education and patients self-management might help healthcare givers timely perform related interventions and help patients reduce their fear of progression thus actively cooperate with T2DM treatments.